GREGORY PALAMAS’ READING OF A SEVENTH-CENTURY PSEUDO-ATHANASIAN HOMILY - LADAS, Anthony (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
During the Palamite controversy of the fourteenth century, the works of the great Fathers of the Church were scoured by both sides of the controversy, which sought to ground their teaching in recognized authorities. Of these works, one of the most frequently cited by Palamites was a pseudonymous Homily on the Annunciation attributed to Saint Athanasius the Great and generally held to have its origin in the seventh century. This article analyzes the Homily’s range of use among the Palamite party before focusing on its most influential section, which discusses those things perceived and named theologically around God as contributing to the totality and fullness of divinity. It examines Gregory Palamas’ use of these terms in his own theological system and then considers how his system may serve to clarify a unique and theologically suspect etymological connection contained within the Homily, deriving οὐσία from ἰσία.